Investigation of Engineering Properties of Cement-Stabilized Calcareous Sand Foundation - Yuan Chai; Dai-Ping Jiang; Fu-Jiang Wang; Hai-Bo Lyu (Advances in Materials Science and Engineering)
Calcareous sand is widespread around Nansha Islands, South China Sea. In oceanic and coastal engineering, calcareous sand is usually used as a building foundation and backfill material for airport runway embankments. The engineering characteristics of calcareous sand is different from terrigenous sand because of its irregular grain shape, lower particle strength, and internal voids, which have caused many engineering problems in the last decades. Cement-stabilized soil, as a common foundation reinforcement method, can solve these engineering problems and improve the foundation strength effectively. Therefore, it is very important to estimate the engineering characteristics of cement-stabilized calcareous sand foundations. In this paper, the basic engineering characteristics, bearing capacity, and deformational behavior of calcareous sand were studied by carrying out a series of tests on cement-stabilized calcareous sand. It is found that: (1) the uniaxial compression strength of calcareous sand is higher than that of Guangzhou soft soil but lower than that of filter medium quartz sand; (2) the deformation of the calcareous sand under compression is mainly plastic, and the elastic deformation gradually increases with increasing cement content; (3) the apparent cohesion of calcareous sand increases, while internal friction angle decreases with increasing cement content; (4) cement-stabilized method can significantly improve the bearing capacity of calcareous sand foundation, especially for the saturated state. A cement content equal to or more than 15% and a thickness of 1/8 of the foundation can effectively improve the bearing capacity of the foundation; and (5) the ultimate bearing capacity of the foundation by numerical calculation is higher than that by experiments, while the settlement by calculating is lower.